Karakteristik penderita benda asing di esofagus di Rumah Sakit Umum Pusat H. Adam Malik Medan Januari 2006-Desember 2011 - Suri Anita; Abdul Rachman Saragih; Linda Irwani Adenin; Ashri Yudhistira (Fakultas Kedokteran USU, 2012)
Introduction : Foreign body ingestion and impaction in the esophagus constitutes an important cause of morbidity and mortality at any groups of age in worldwide.Objective : To determine the characteristic of esophageal foreign bodies in H. Adam Malik General Hospital Medan from January 2006 – December 2011.Methods : A descriptive study applying medical records of patients who were hospitalized for foreign body ingestion from January 2006 – December 2011.Result : One hundred and thirteen medical records was collected (71 males and 42 females) aged of 4 month – 75 years old, with mean 16.8 years old, were admitted with the diagnosis of esophageal foreign body. The most clinical symptoms was dysphagia 43.3% and odynophagia 28.2% from total symptoms. Anorganic was the most common foreign bodies 92% and organic 8%. The most common site of impaction were upper third 92.9%. The duration of impaction 44.2% was 6-24 hours. 92.9% with >24 hours length of time from diagnosed to the esophagoscopy procedure. Complication were noted in 5.4%. There was significant relation between age and type of foreign body and between age and location of impaction (P <0.05). Conclusion : The characteristic of esophageal foreign body were collected and found that there was significant relation between type of foreign body and age, site of impaction also.Keywords: foreign bodies; esophagus; esophagoscopy; characteristic